Degradation of voltage-current characteristics of gallium phosphide diodes due to radiation-induced defects - Dubovyi, V.K.; Kanevsky, S.O.; Litovchenko, P.G.; Opilat, V.Ya.; Tartachnik, V.P. (Functional Materials, 2005)
The GaP diode radiation-induced degradation has been established to be caused mainlу bу the reduction of the current carrier lifetime resulting from introduction of non-radiative deep levels of the radiation-induced defects. A thin structure has been revealed in the voltage-current characteristics (VAC) at temperatures lower than 90 К. The existence of oscillations are associated with the capturing of non-equilibrium current carriers bу traps followed bу thermal destruction thereof. A characteristic VAC feature of the neutron-irradiated samples is the occurrence of an N-like of negative differential resistance. This deviation from the VAC monotonicitу is explained bу thermallу-induced transformations of the disorder areas. Установлено, что главной причиной радиационной деградации GaР-диодов является уменьшение времени жизни носителей тока в результате введения безызлучательных глубоких уровней радиационных эффектов. Выявлено тонкую структуру вольт-амперной характеристики (ВАХ) диодов в области температур ниже 90 К. Существование осцилляций связывается с захватом неравновесных носителей тока ловушками и их последующим термическим опустошением. Характерной особенностью ВАХ образцов, облученных нейтронами, есть возникновение N-образного участка отрицательного дифференциального сопротивления. Наличие таких отклонений от монотонности ВАХ объясняется термическими преобразованиями областей разупорядочення. Встановлено, що головна причина радiацiйної деградацiї GaP-дiодiв - зменшення часу життя носiїв струму в результатi уведення безвипромiнювальних глибоких рiвнiв радiацiйних дефектiв. Виявлено тонку структуру вольт-амперних характеристик (ВАХ) дiодiв в областi температур нижче 90 К. Iснування осциляцiй пов'язується iз захватом нерiвноважних носiїв струму пастками та їх наступним термiчним спустошенням. Характерною особливiстю ВАХ зразкiв, опромiнених нейтронами, є виникнення N-подiбної дiлянки вiд'ємного диференцiального опору. Iснування цього вiдхилення вiд монотонностi ВАХ пояснюється термiчними перетвореннями областей розупорядкування.